Stagnant Dreamers : How the Inner City Shapes the Integration of the Second Generation. - Rendon, Maria G. (Russell Sage Foundation, 2019)
"Stagnant Dreamers captures the story of Latino young men often labeled "at risk" due to their race/ethnicity, gender, and zip-code, who are at a crossroad, attempting to integrate into the larger American context and carve out a space in its dwindling middle class. It follows the lives of forty-two male offspring of post-1965 Latino immigrants from two high poverty neighborhoods in Los Angeles as they transition into adulthood. This study shows how America's urban violence and social isolation in segregated contexts shape the integration process of young men, calling attention to underappreciated resources that exist in these communities that mitigate the negative impacts of growing up in America's poorest neighborhoods. It explains why some young men get ahead, while others sink deeper into poverty. In the process, it reveals how Latino immigrants and their young adult children alter their neighborhoods, becoming part of Los Angeles's resilient working class"--